2016
DOI: 10.3892/etm.2016.3630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polygonatum odoratum extract on human breast cancer MDA-MB-231 cell proliferation and apoptosis

Abstract: Abstract. Traditional Chinese medicine (TCM) is important in the provision of anti-tumor drugs. Recently, studies have shown that certain types of TCM agents are able to control the growth of tumors, enhance the body's immune function and enhance the therapeutic effect of chemotherapeutic drugs. In women, breast carcinoma is the most common tumor type and the second most common cause of death from cancer. Polygonatum odoratum (P. odoratum) is commonly used in TCM. The aim of the present study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…This component showed cytotoxic effect on murine fibrosarcoma L929 and melanoma A375 cancer cells by interrupting of a mitochondria-mediated ROS-p38-p53 pathway and this caused the growth inhibition of cancer cell lines (19,20). P. odoratum extracts showed growth inhibition properties on human breast cancer MDA-MB-231 cells and induced apoptosis (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This component showed cytotoxic effect on murine fibrosarcoma L929 and melanoma A375 cancer cells by interrupting of a mitochondria-mediated ROS-p38-p53 pathway and this caused the growth inhibition of cancer cell lines (19,20). P. odoratum extracts showed growth inhibition properties on human breast cancer MDA-MB-231 cells and induced apoptosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…The rhizome of Polygonatum is used as an herbal medicine in traditional medicine. The anti-depressant, anti-inflammatory, anticancer, anti-fever, antioxidant, and antimicrobial activities of the Polygonatum rhizome have been shown in many studies (9,10). Variety of compounds such as polysaccharides, saponins, phytohormones, glycosides, flavonoids, and alkaloids have been isolated from Polygonatum rhizome.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus membranaceus (Huangqi) has a wide range of immunopotentiating effects and is widely used as an adjuvant medicine during cancer therapy (19). Polygonatum odoratum (yuzu) extracts induce apoptosis of MDA-MB-231 breast cancer cells (20) and A549 human lung cancer cells (21). Extracts of scolopendra (tianlong) subspinipes mutilans induce cell cycle arrest and apoptosis in A375 human melanoma cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicinal herbs have been used for the treatment of various diseases in China and Southeast Asia (23). Also, many studies have focused on the anticancer effects of phytochemicals which is contained in natural plant (3,(7)(8)(9)(10). In the present study, we examined whether ethanol extracts from C. monnieri (CME)-induced apoptotic and cell cycle arrest effects were occurred by p53-dependent or p53-independent mechanism in HepG2 (wild-type p53) and Hep3B (p53-null) hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that bioactive compounds from natural plant extracts play a crucial role as potential therapeutic agents (6). Many plant extracts induce anticancer effects such as anti-proliferative and anti-metastatic effects and cell cycle arrest in various cancer cell lines (7)(8)(9). Moreover, the anticancer activity of natural plant extracts has been investigated in HepG2 and Hep3B hepatocellular carcinoma cells (3,10).…”
Section: Introductionmentioning
confidence: 99%